Antropologia w świetle wcielenia: chrześcijańska wizja natury ludzkiej w procesie formowania doktryny chrystologicznej w II-V wieku - Kashchuk, Oleksandr (Vox Patrum, 2025)
The aim of this article is to verify the continuity and development of the Church Fathers’ reflection on human nature in the light of the Incarnate Christ and to present its evolution during the period from the 2nd to the 5th century. Employing a panoramic and synthetic approach enabled the identification of those anthropological elements that were common and consistently emphasized, thereby highlighting the essential core of the doctrine. The study focuses on the anthropological implications of the Incarnation, that is, the fact that God truly assumed human nature: body, soul, and reason. Based on the testimonies of the Church Fathers – from Ignatius of Antioch and Irenaeus of Lyon to the definition of the Council of Chalcedon – It is demonstrated that theology in the 2nd to 5th centuries consistently argued for the real and inseparable presence of both the fullness of divinity and the fullness of humanity in the one person of Jesus Christ. The analysis addresses four main theological traditions: Alexandrian, Cappadocian, Antiochene, and Western (Latin), each of which defended the integrity of Christ’s divine-human identity in a distinct manner. Within these Christological currents, a deepened vision of humanity gradually emerged – conceived as a nature capable of union with God without losing its own identity. The article shows that Christology constituted the foundation of Christian anthropology: it defined not only the identity of Christ but also the dignity of the human person and his capacity to participate in the life of God. In this perspective, the Incarnation appears as the key to understanding the mystery of humanity.